Leadership in Small and Medium Enterprises in Unique Snack Industries (Case Studies in Yogyakarta) - Jaya Addin Linando.; Arif Hartono.; Trias Setiawati. (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2018)
Yogyakarta is a unique city in Indonesia where there are a lot of good and creative products produced by small and medium enterprises (SMEs). According to resource-based theory, good and unique products come from good management within the company. The assumption is that leaders in unique snack food industries are good leaders. This study examines the definition of 'leadership' in the perspective of SMEs and the nature and skills needed to be good leaders in SMEs. This study also examines the process of forming leadership from leaders in SMEs. So readers not only know what is needed to be a good leader, but also understand how these leaders get those qualities, what they did in the past, and how their past experiences make them good leaders currently. This study found that there are four main elements of leadership, namely: leaders, followers, interactions, and goals. This study also found eight main characteristics or skills needed to be good leaders in SMEs, they are: influential, able to bridge, willing to learn, visionary, persistent, able to motivate, determine and confident